2014
DOI: 10.1186/s40359-014-0034-3
|View full text |Cite
|
Sign up to set email alerts
|

The developmental relationship between language and motor performance from 3 to 5 years of age: a prospective longitudinal population study

Abstract: Background: Previous research has found that language and motor skills are closely interrelated developmental areas. This observation has led to questions about the specificity of these domains, and the nature of the associations. In this study, we investigated the longitudinal relationship between language and gross and fine motor performance from 3 to 5 years of age. Methods: We tested the prediction across and within developmental domains using cross-lagged panel models. In addition, estimates of specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 49 publications
2
39
0
13
Order By: Relevance
“…Previous studies of general populations have provided inconsistent findings regarding children's developmental pathways. Some studies report high stability in early development and suggest that early signs of developmental impairment are markers for further developmental difficulty (Rescorla ; Bornstein & Putnick ; Wang et al ). Other studies show heterogeneity in early development with considerable variability in developmental patterns (Darrah et al ; Roze et al ; Ukoumunne et al ; Nishimura et al ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of general populations have provided inconsistent findings regarding children's developmental pathways. Some studies report high stability in early development and suggest that early signs of developmental impairment are markers for further developmental difficulty (Rescorla ; Bornstein & Putnick ; Wang et al ). Other studies show heterogeneity in early development with considerable variability in developmental patterns (Darrah et al ; Roze et al ; Ukoumunne et al ; Nishimura et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Developmental delay (DD), characterized by late achievement of developmental milestones, affects approximately 5–15% of all children in the general population (Boyle et al ; Valla et al ). Although most children seem to catch up on developmental skills in early and middle childhood (Rescorla ), there are some children in whom DD persists or even increases during this period (Bornstein & Putnick ; Wang et al ). DD is of importance, not only because of its association with medical and genetic conditions and the consequences it bears in itself but also because of the frequency of associated problems, including emotional and behavioural problems (Baker et al ; Emerson & Einfeld ) and poor educational achievement (Blanchard et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Language skills was found to be associated with motor skills at both 1 ½, 3 and 5 years of age, and when controlling for the stability of development within each developmental domain motor skills at 1 ½ years of age still had a unique association to language skills at three years of age (17). From 3 to 5 years of age, controlling for the stability of each developmental domain the researchers found that language skills at three years of age uniquely predicted motor skills at five years of age, over and above what could be explained by earlier motor skills (18). Ribeiro and colleagues studied language development in children born preterm, and found that attention problems has a precursor role to language development in premature children (15).…”
Section: Growth and Change In Language Development And Risk Factors Fmentioning
confidence: 89%
“…Finally, there is research showing that both gross motor [Bedford, Pickles, & Lord, ] and fine motor ability [Sauer LeBarton & Iverson, ] predict larger expressive language ability in children with or at risk for ASD [but see also Wang, Lekhal, Aaro, Holte, & Schjolberg, ]. However, around the time of canonical babbling onset, when children begin to produce consonant‐vowel syllables and strings of syllables (between 6 and 10 months in typically developing infants), there is also a significant increase in rates of rhythmic upper limb movement—that is, simultaneous banging and babbling [Iverson & Fagan, ; Iverson & Wozniak, ].…”
Section: Subphonemic Variation In Typical Development: the Voiced/voimentioning
confidence: 99%